Letters of William Archer - Archer, William Henry, 1825-1909.; Smyth, Patrick, Rev. (1847)
48 letters covering the period 1847-1866 from a number of correspondents, including John Pascoe Fawkner, Raffaello Carboni, Rev. P. Smyth, Robert Hoddle and C. J. Tyers, concerning explorations, latitudes, the Eureka stockade, meteorology, registration systems, etc.
Manuscript reference no.: NLA MS 264.
Available also on microfilm.
Also available online
In 1853 William Archer was employed in Melbourne as Assistant Registar-General drafting a comprehensive system of legal and statistical registration. He became Registrar-General in 1862.
Descriptive list available.
Exhibited: "Treasures Gallery", National Library of Australia, 3 December 2012 - 3 May 2013.
Keywords: Archer, William Henry, -- 1825-1909 -- Correspondence; Eureka Stockade, Ballarat, Vic., 1854; Meteorology -- Victoria; Victoria -- Officials and employees -- Correspondence; Australia -- Discovery and exploration; Correspondence; Public servants